A new look into the arcaheological materials from the Museum of Évora, Portugal - the case study of the Zambujeiro Dolmen - Manhita, Ana (2019)
This paper presents the results of a multidisciplinary and multi-analytical study of the amber beads, red pigments, lithic arrowheads and selected ceramics from the Museum of Évora’s collection of the Zambujeiro Dolmen. Amber beads were studied by Attenuated Total Reflectance Fourier Transformed Infrared Spectroscopy (ATR-FTIR) and Pyrolysis coupled to Gas Chromatography and Mass Spectrometry (Py-GC/MS) to confirm their chemical nature and provenance. The red pigments, frequently found in funerary Neolithic context of the Iberian Peninsula, were studied with micro-Raman, and Scanning Electron Microscopy coupled to Energy Dispersive X-Ray Spectroscopy (SEM-EDS) to identify their chemical nature and provenance. The lithic arrowheads were analysed by portable X-Ray Fluorescence (p-XRF), micro X-Ray Diffraction (XRD), SEM-EDS, and Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS). The ceramic materials were studied to infer provenance and production technology by p-XRF, XRD and SEM-EDS; ceramic contents were evaluated by GC/MS. The studies have shown that while some materials travel hundreds or thousands of kilometres to arrive to the Zambujeiro Dolmen, local materials were also used in the items selected by the communities to honour their deceased.